2021
DOI: 10.1096/fj.202002420r
|View full text |Cite
|
Sign up to set email alerts
|

Single‐cell transcriptomics reveal temporal dynamics of critical regulators of germ cell fate during mouse sex determination

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 103 publications
8
50
0
Order By: Relevance
“…We found that the expression profiles of migrating PGCs (at E2.5) resemble those of colonized PGCs (at E6 in males and at E6–E8 in females). In mice, it is known that the transcriptomes of XX and XY cells overlap at the early developmental stage, whereas sex-specific branches are formed in the differentiated cells at the late stages [100] . However, in this study, chickens showed differences in transcriptome levels between mS1 and fS1 (early-stage germ cells).…”
Section: Discussionmentioning
confidence: 99%
“…We found that the expression profiles of migrating PGCs (at E2.5) resemble those of colonized PGCs (at E6 in males and at E6–E8 in females). In mice, it is known that the transcriptomes of XX and XY cells overlap at the early developmental stage, whereas sex-specific branches are formed in the differentiated cells at the late stages [100] . However, in this study, chickens showed differences in transcriptome levels between mS1 and fS1 (early-stage germ cells).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic sexing was performed by PCR, as described previously ( 61 ). Urogenital ridges including both the gonads and mesonephros (E10.5, E11.5) from both sexes, and testes or ovaries (E12.5-E16.5), were isolated at each time point and enzymatically dissociated as described previously ( 62 ). Approximately 5000 single cells were loaded on a 10x Chromium instrument and scRNA-seq libraries were prepared using the 10X Genomics Chromium Controller and Chromium Single Cell 3’ Library & Gel Bead Kit V2, as per the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Genetic sexing was performed by PCR, as described previously (61). Urogenital ridges including both the gonads and mesonephros (E10.5, E11.5) from both sexes, and testes or ovaries (E12.5-E16.5), were isolated at each time point and enzymatically dissociated as described previously (62). Approximately 5000 single cells were loaded on a 10x…”
Section: Sample Collection and Single Cell Transcript Profilingmentioning
confidence: 99%
“…We can generate high quality early gonadal progenitors and Sertoli-like cells. The system could be refined further to produce other somatic lineages of the gonad, such as Leydig and peritubular myoid cells of the testis or granulosa and theca cells of the ovary, as well as other gonadal lineages that are being identified by single-cell sequencing approaches (Mayere et al, 2021;Stevant et al, 2019;Stevant et al, 2018). Recently, foetal ovarian somatic cell-like cells (FOSLCs) were derived from mESC, using an approach similar to ours.…”
Section: Discussionmentioning
confidence: 99%